A Regression on Climate Policy - The European Commission's Proposal to Reduce CO2 Emissions from Transport - Manuel Frondel; Christoph M. Schmidt; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
As part of its efforts to reach the targets of the Kyoto Protocol, the European Commission is currently considering a new directive to reduce the per-kilometer CO2 emissions of newly registered automobiles. This paper critically assesses this proposal with respect to its economic and technological underpinnings. We argue that the proposal's reliance on targets based on per-kilometer emissions not only conceals the true costs of compliance and thereby stifles informed public discourse, but is also less cost-effective than alternative measures such as emissions trading. We further examine the proposal's underlying assumptions, finding that these misrepresent the current state of automotive technology and therefore may overestimate the feasibility of achieving the suggested emissions targets. Alternative targets are consequently proposed that are argued to more accurately reflect the industry's technological evolution to date.
Keywords: L98; Y10; 330; Technological progress; private automobiles; efficiency standards; Umweltverträgliche Verkehrspolitik; Personenkraftwagen; Abgastechnik; Normung; EU-Umweltpolitik; Klimaschutz; Technischer Fortschritt; Kosten-Nutzen-Analyse; EU-Staaten